P2Y12 expression on microglia in the human brain. Issue 4 (28th July 2016) - Satoh, Jun‐ichi; Tosaki, Youhei; Sakai, Kenji; Yanaizu, Motoaki; Kino, Yoshihiro
Abstract : P2Y12 expressed on ramified and amoeboid microglia in the human brain. P2Y12 is not expressed on perivascular macrophages. P2Y12‐immunoreactive ramified microglia are not polarized to M1 or M2 in NHD brains.